Al18F-NOTA-folate PET for imaging of inflammation in calcific aortic valve disease - Malmer, Erki (My University, 2025)
Calcific aortic valve disease (CAVD), along with its clinical presentation as aortic valve stenosis (AS), especially affects elderly population. The progression of AS occurs in two stages: an initial phase characterized by endothelial injury, lipid accumulation, and inflammation, followed by a subsequent phase dominated by calcification-promoting factors. Macrophages are central to both the inflammatory response and the advancement of calcification. Folate receptor beta (FR-β), expressed on activated macrophages, has been targeted for positron emission tomography (PET) imaging to detect inflammation in atherosclerosis and autoimmune myocarditis. However, its use in CAVD has not been explored. The aim of this study was to evaluate whether a PET tracer Al18F-NOTA-folate enables detection of inflammation in experimental CAVD. LDLR-/-ApoB100/100 mice on a high-fat diet for 8 months (CAVD model) and age-matched controls were studied. Echocardiography was performed to assess the AS severity. Then mice underwent both 18F-NaF (microcalcification) and Al¹⁸F-NOTA-folate PET imaging. Al¹⁸F-NOTA-folate uptake was further analysed with ex-vivo autoradiography and immunohistochemistry. Echocardiography demonstrated significant AS in the CAVD compared to controls. Moreover, PET imaging with Al¹⁸F-NOTA-folate revealed higher uptake in CAVD valve leaflets compared to controls and immunohistochemistry identified continuous Mac-3 positive macrophage areas in CAVD valves. In conclusion Al¹⁸F-NOTA-folate PET can detect inflammation in the aortic valve region of an experimental CAVD mouse model and may be a promising tool for assessing early-phase disease. However, further detailed investigation is needed to determine the precise origin of the signal observed in PET/CT imaging.
Keywords: Calcific aortic valve disease (CAVD), Al¹⁸F-NOTA-folate PET, folate receptor beta (FR-β), macrophages